Analysis of the Quality of Natural Dyes in Weaving Exposed to Sunlight Using MSE and PSNR Parameters - Patrisius Batarius; Alfry Aristo Sinlae; Elisabeth F. Fahik (Ikatan Ahli Informatika Indonesia (IAII), 2022)
It is widely assumed that natural dyes in weaving degrade in quality when exposed to sunlight for an extended period. This indication is visible to the naked eye. There is currently no standard for evaluating the quality of natural dyes. The Boti tribe's weaving on Timor Island, East Nusa Tenggara Province, is one type of weaving that uses natural dyes. The dye is made from corn flour and a combination of